Rhetorical analysis of the prosecution’s speech at the Recife jury court and its relation to the difficulties for effectiveness and human rights violations - Lima, Pedro Parini Marques de (2022)
This article is the result of a scientific research carried out with funding from the Foundation for the Support of Science and Technology of the State of Pernambuco between 2017 and 2018. It consisted of a field research carried out in the 4th Court of the Capital Jury Tribunal, following judgments from participation as a member of the Popular Jury and carrying out a rhetorical analysis of the speeches made by the Public Prosecutor of Pernambuco in the plenary. The relevance of using analytical rhetoric as a method for the study of law was demonstrated, more consistent with the particularities of the area. With the analysis, it was possible to make a comparison between the institutional function of the organ and the speeches made that stand against what is normatively the legal discourse on human rights. It demonstrated the importance of rhetoric in the study of law and the power of language for the effectiveness of the rights said to be guaranteed to all, but in fact relegated within the scope of Criminal Justice. In another sense, there was a mismatch between basic conceptions preached by human rights and the speeches made by members of the Public Ministry, which has the defence of fundamental rights as an institutional function, identifying problems that can help in directing the possibilities for realizing the human rights, mainly in the materialization of basic rights and guarantees of people who respond to criminal proceedings.